2018
DOI: 10.1002/slct.201803149
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis of TiO2 Nanowires‐Reduced Graphene Oxide Nanocomposite to Enhance Electrochemical Performance in Supercapacitor

Abstract: In this paper, uniform TiO 2 nanowires (TiO 2 NWs) on reduced graphene oxide (RGO) nanosheets were successfully synthesized by a simple and low-cost hydrothermal method. The high capacitance (202.5 F⋅g À 1 at 1 A⋅g À 1 ) and excellent cyclic stability (81.9% capacity retention after 5000 cycles) were achieved for TiO 2 NWs-RGO nanocomposite as supercapacitor electrode. The excellent electrochemical performance is due to the synergistic effect of one-dimensional TiO 2 NWs with chemical stability and RGO with ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Bokhari et al 28 synthesized a hybrid composite of reduced graphene oxide (rGO)/TiO 2 with 334 F g −1 at 0.1 A g −1 . Yue et al 29 reported a hydrothermal method to develop TiO 2 nanowire/rGO nanocomposites and a high capacitance of 202.5 F•g −1 at 1 A•g −1 was obtained. Cheng et al 30 synthesized amorphous Co 2 SiO 4 nanobelts by a template method.…”
Section: Introductionmentioning
confidence: 99%
“…Bokhari et al 28 synthesized a hybrid composite of reduced graphene oxide (rGO)/TiO 2 with 334 F g −1 at 0.1 A g −1 . Yue et al 29 reported a hydrothermal method to develop TiO 2 nanowire/rGO nanocomposites and a high capacitance of 202.5 F•g −1 at 1 A•g −1 was obtained. Cheng et al 30 synthesized amorphous Co 2 SiO 4 nanobelts by a template method.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, by annealing the H 2 TiO 3 NWs at 450 °C in air for 2 h, they were converted into TiO 2 NWs. Studies have reported the growth mechanism of TiO 2 NWs in the following manner. Curving and wrapping nanosheets (NSTs) to NWs. For the curving of NSTs, Zhang et al suggested that an asymmetrical chemical surrounding is induced by the imbalance of H + or Na + ion concentration on the various titanate NST sites.…”
Section: Resultsmentioning
confidence: 99%
“…In the meanwhile, the electrolyte can be balancing and transferring charges between the plates. This type of supercapacitor is used in many areas, such as transportation, electronic devices, and satellites, owing to their high stability, fast charge and discharge proficiency, and high power density. …”
Section: Introductionmentioning
confidence: 99%